Islamic financial innovation: tools and trends / viewpoints by guest author Humayon A. Dar. - Dar, Humayon A. (Universiti Teknologi Mara Selangor, 2013)
In a business context, innovation is of two types: model innovation and process innovation. Model innovation involves developing new instruments and methods (inputs) to achieve new objectives (outputs), which must bring new business and hence improve profitability. Process innovation is, in general, an incremental process that utilises existing instruments and methods in new formats and permutations to achieve desired objectives, goals and outcomes in a more efficient and cost effective way. In a business context, it will still be considered as an innovation if a desired outcome is achieved by utilising the same existing instruments and methods with no increased efficiency or cost effectiveness, as long as the new format and permutation result in increased profits.